A New Approach to Research Data Management with a Focus on Traceability: Adacta. Issue 11 (2nd September 2022) - Gossler, Hendrik; Riedel, Johannes; Daymo, Eric; Chacko, Rinu; Angeli, Sofia; Deutschmann, Olaf
Abstract: Traceability between samples, devices and data is of great importance to the catalysis community. Adacta is a new research data management (RDM) system designed to create a traceable digital twin of a testing environment, not only storing data, but also creating a readily retrievable time‐accurate record of the critical components used to measure catalyst performance. Future developments include extending Adacta to interact with electronic laboratory notebooks and to spawn simulations directly using data and measurements stored in the database. Abstract : Adacta is a new research data management tool that creates a time accurate digital twin of a sample and the experimental devices used for its evaluation. The connections between resources (e.g., data), devices and samples can be readily interrogated, ensuring full traceability of an experimental system.